Technogenic soil as a long-term factor for spring water contamination (by the example of Moscow region) - A A Rasskazov (RUDN Journal of Engineering Researches, 2013)
In article the results of the research work of series of springs are stated. Regularity of change of spring water quality under the influence of man-caused factors is revealed. Such factors as geological structure of rocks, sorption characteristics, presence of technogenic soil etc., have a significant impact on the presence of contaminants in spring water. The complex approach enables to optimize the actions for spring water pollution prevention.